Scandal of the summer - Vasti, Alexandra (St. Martin's Griffin, 2026)
"A desperate debutante meets a ragtag smuggler in this sexy Regency romp by USA Today bestselling author Alexandra Vasti. Eccentric heiress Lady Ruby Ballimore has had enough of the Marriage Mart. After offending yet another Very Important Marquess -- and imperiling her father's diplomatic career -- Ruby flees London for the holiday house of a glamorous (and better yet, absent) princess. Armed with a forged invitation and accompanied by her like-minded friends, Ruby arrives at the Cornwall estate expecting a summer of blissful freedom. Instead, she discovers a derelict mansion and the most suspiciously charming man she's ever met. Former privateer and current con artist Captain Malcolm Archer has dragged his ramshackle crew into a new life. Posing as staff at a princess's abandoned estate provides the perfect cover for Archer's smuggling scheme (not to mention free rent). Everything's going according to plan -- until an unorthodox London heiress crashes the party. But when Archer and his crew attempt to frighten off their uninvited guests, Ruby's unfazed by insect invasions and sham sea monsters. Harder to ignore? The scorching heat between the rakish pirate and the debutante who can see right through him. As sparks fly, deceptions run wild-because in this Great Cornish Fake Off, the only thing riskier than telling the truth is falling in love." -- Provided by publisher.